A Multi-Functional Reconfigurable Low-Power Ultra-High PSRR CMOS Reference-System - Söll, Christopher; Bänisch, Andreas; Röber, Jürgen; Shi, Lan; Weigel, Robert (IEEE Conference on PhD Research in Microelectronics and Electronics (PRIME), 2015)
This paper presents a new reference system with emphasis on low power design and high power supply rejection. The untrimmed reference provides a 600mV output voltage, which only differs by 5.75mV in the temperature range between -40 ◦ C and +125 ◦ C and a PSRR of -157.2 dB at 10Hz. The core part of the reference produces a reference potential of 416.1mV with a deviation of only 1.59mV. Moreover, the circuit provides a 900mV output, a temperature independent 3 μA current and trimming possibilities for the temperature curves and the amplitude of output voltages and currents. Under all operating conditions, the post-layout Corner- and Monte-Carlo-Simulations show a power consumption of less than 40 μA and ensure functionality across process, supply voltage and temperature variations.
elib2cris::1512001600,soell2015
Keywords: bandgap; reference; low power; high psrr; temperature coefficient; subregulation; GRK-1773